Generation of neutralizing and non-neutralizing monoclonal antibodies against H7N9 influenza virus - Fan Yang; Yixin Xiao; Rufeng Lu; Bin Chen; Fumin Liu; Liyan Wang; Hangping Yao; Nanping Wu; Haibo Wu (Emerging Microbes and Infections, 2020)
ABSTRACTThe H7N9 viruses have been circulating for six years. The insertion of a polybasic cleavage site in the haemagglutinin (HA) protein of H7N9 has resulted in the emergence of a highly pathogenic (HP) avian influenza virus. Currently, there are limited studies on neutralizing monoclonal antibodies(mAbs) against HP H7N9 AIVs. In this study, mice were immunized with inactivated H7N9 vaccine of A/ZJU01/PR8/2013 to produce murine mAbs. Finally, two murine mAbs against the HA of low pathogenic (LP) virus were produced and characterized. Characterization included determining mAbs binding breadth and affinity, in vitro neutralization capacity, and potential in vivo protection. Two of these mAbs, 1H10 and 2D1, have been identified to have therapeutic and prophylactic efficacy against the HP strain in mouse passive transfer-viral challenge experiments. The mAb 1H10 was most efficacious, even if the treatment-time was as late as 72 h post-infection, or the therapeutic dose was as low as 1 mg/kg; and it was confirmed to have haemagglutination inhibition and neutralizing activity on both LP-and HP-H7N9 strains. Further study indicated that the protection provided by 2D1 was mediated by antibody-dependent cellular cytotoxicity. The mAbs described here provide promising results and merit further development into potential antiviral therapeutics for H7N9 infection.